Feedforward-plus-proportional–integral–derivative controller for agricultural robot turning in headland. (8th January 2020) - Huang, Peichen; Zhang, Zhigang; Luo, Xiwen
Traveling along straight lines and headland turning are two common motions during the automatic guidance of agricultural machines. However, most studies focus on accurately following parallel tracks in the field and seldom consider the maneuvers at the end of each row. Moreover, numerous studies have mainly focused on planning the global trajectories in the entire field to increase field efficiency, and very few works are related to maneuver generation and vehicle control in headlands. In this study, a feedforward-plus-proportional–integral–derivative controller for a differential drive robot in headland turning was developed. The feedforward-plus-proportional–integral–derivative controller consisted of a feedforward and a feedback loop. The feedforward loop was designed based on the heading errors of a lookahead point on the planning path. The feedback loop was designed based on radial errors to improve the tracking accuracy. Field comparison tests of feedforward, feedback, and feedforward-plus-proportional–integral–derivative controllers were conducted. Experimental results showed that the feedforward-plus-proportional–integral–derivative had better tracking results and took less turning time.